Slippers at Home - Clements, Andrew 1949-; Bynum, Janie (New York : Dutton Children's Books, 2004)
Slippers the puppy loves each of the four people who share his home.
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Animals -- Fiction -- Infancy; Human-animal relationships -- Fiction; Dwellings -- Fiction